Rework in civil construction projects at design phase: Influencing factors and suggested solutions - Van Tuan Cao; My Pham Truong; Ngoc Loi Dang (CTU Journal of Innovation and Sustainable Development)
Among the various project phases, the design phase often contains errors that result in rework in civil construction projects. This rework can lead to budget overruns, schedule delays, and a decline in construction quality. There is rare knowledge of reworks in civil construction projects, especially in the design phase. This paper presents an overview of the influencing factors and solutions for reworks in civil construction projects at the design phase. To achieve this objective, a survey on the causes of rework was conducted with experts experienced in designing and constructing civil projects in southern Vietnam. Civil engineers and investors involved in the project at the design phases were targets of the survey. Five groups, including designers, design managers, investors, subcontractors, and objective conditions, were selected for designing survey questionnaires. Then, the PCA (principal component analysis) was applied to the collected data to reveal the most influencing factors on rework causes. Based on the results obtained, several suggestions are proposed to minimize rework in civil construction projects. These findings can serve as valuable insights for investors and design consultants, fostering learning and process improvements to reduce rework in future projects.